046 A Novel Artificial Conduit for Peripheral Nerve Regeneration Rescues Erectile Function after Cavernous Nerve Injury. (1st May 2022) - Kobayashi, K.; Takayanagi, A.; Hashimoto, K.; Tanaka, T.; Masumori, N.
ABSTRACT: Introduction: Postoperative erectile dysfunction after radical prostatectomy can occur due to surgical injury of the cavernous nerves, which can adversely affect quality of life. Objective: We evaluated the treatment effects of a novel artificial conduit for peripheral nerve regeneration (Nerbridge), which is commercially available, on erectile dysfunction in a cavernous nerve injury model. Methods: Male Sprague-Dawley rats were used this study. The rat cavernous nerve was resected bilaterally. We interposed a nerve gap with the artificial conduit as a treatment group. After resecting the rat cavernous nerve, we did not do any treatment in an untreated group. Sham-operated rats were used as a control group. We measured the intracavernous pressure (ICP) and arterial pressure (AP) at 8 weeks after surgery in these 3 groups. Results: In the untreated group, ICP/AP was significantly decreased compared to that in the control group (mean ICP/AP: 0.138 vs. 0.566, respectively; p<0.05). On the other hand, ICP/AP in the treated group (mean: 0.284) was not significantly decreased compared to that in the control group. Conclusions: The commercially available artificial conduit may prevent the decrease in erectile function after cavernous nerve injury. Disclosure: Work supported by industry: no.